Growing together: making Lithuania's convergence process more inclusive - Demmou, Lilas (OECD Economics Department Working Papers, 2016)
Although Lithuania's growth has been impressive, inequality is high, the risk of poverty is one of the highest of European countries, and life expectancy is comparatively low and strongly dependent on socio-economic background. The low job satisfaction reduces well-being and feeds high emigration. Labour market, social and health policies can all contribute to improve both well-being and growth. Priorities include providing more and better jobs for all, especially for the low-skilled, by making work pay while keeping the labour costs under control. More accessible and adequate income support combined with more ambitious job-search support and training programmes would better-integrate out-of-work individuals into the labour market. Strengthening equity, effectiveness and sustainability of health policies is also instrumental to inclusiveness. This Working Paper relates to the 2016 OECD Economic Survey of Lithuania (www.oecd.org/eco/surveys/economic-survey-lithuania.htm)